PENGARUH MINDFULNESS DAN MANAJEMEN WAKTU BELAJAR DI KELAS TERHADAP HASIL BELAJAR IPS SISWA UPTD SMP NEGERI 5 PEMATANGSIANTAR - Tia Ivanka Fitri Siahaan; Anggun Tiur Ida Sinaga; Benjamin Albert Simamora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of mindfulness and students’ study time management at school on the social studies learning outcomes of students at UPTD SMP Negeri 5 Pematangsiantar. This study was motivated by the low learning outcomes of students, who have not yet achieved an adequate learning completion rate, as well as their weak mindfulness and study time management.This is a quantitative study using a descriptive quantitative data analysis approach. The study population consists of all 536 students at UPTD SMP Negeri 5 Pematangsiantar. The sample size is 84 students. Simple random sampling was used. Data were collected via a questionnaire.The results of the study indicate that mindfulness does not have a significant effect on student learning outcomes, as evidenced by the t-test showing t-calculated < t-table (-0.125 < 1.663). Study time management has a significant effect on learning outcomes, as evidenced by the t-test showing t-calculated > t-table (4.196 > 1.663). Mindfulness and study time management together influence students’ learning outcomes; this result is evident from the F-test, which shows that the calculated F-value (14.961) is greater than the critical F-value (3.11) with a significance level of 0.001 < 0.05. The coefficient of determination was found to be 0.270, indicating that 27% of student learning outcomes at UPTD SMP Negeri 5 Pematangsiantar are influenced by mindfulness and study time management. The remaining 73% are influenced by other variables not examined in this study.